ANALISIS PENGAWASAN PENYELENGGARA PERDAGANGAN MELALUI SISTEM ELEKTRONIK (PPMSE) DALAM MENGAWASI FENOMENA BARANG PALSU DI PLATFORM MARKETPLACE (STUDI PERBANDINGAN DI INDONESIA DAN AMERIKA SERIKAT) - Hessa Arteja; Christine S.T. Kansil (Jurnal Hukum Adigama, 2020)
The United States and Indonesia each have recognized the so-called marketplace platform. Marketplace platform is a place where sellers and buyers as consumers for platform providers or PPMSE can make buying and selling transactions online. The marketplace platform is also easily accessible anywhere by the public, therefore many counterfeit goods are sold on the marketplace platform, so that supervision is needed from PPMSE or platform providers as people or business entities that provide and facilitate electronic buying and selling transactions. To answer these problems, the author uses normative legal research methods. Based on the research results, if there are counterfeit goods on the marketplace platform, PPMSE in Indonesia and the United States are not responsible if there are counterfeit goods on the marketplace platform if the platform provider or PPMSE is not the party selling the counterfeit goods and PPMSE or the platform provider has taken the appropriate steps established legal rules. Then the equation of the legal rules regarding platform providers in Indonesia and the United States is that the platform providers both do not monitor and are not responsible for the list of goods sold on the marketplace platform on a regular basis. The difference is that in the Indonesian law regarding PMSE, the cooperative attitude of PPMSE is not regulated if there is a complaint or lawsuit from the owner of the rights, whereas in the United States law, it regulates how PPMSE should behave when the owner of the right to file a subpoena from the court against the platform provider regarding the sale of goods fake on the marketplace platform.